2010
DOI: 10.1158/0008-5472.can-09-2587
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Inhibit T-Cell Activation by Depleting Cystine and Cysteine

Abstract: Myeloid-derived suppressor cells (MDSC) are present in most cancer patients and are potent inhibitors of T-cell-mediated antitumor immunity. Their inhibitory activity is attributed to production of arginase, reactive oxygen species, inducible nitric oxide synthase, and interleukin-10. Here we show that MDSCs also block T-cell activation by sequestering cystine and limiting the availability of cysteine. Cysteine is an essential amino acid for T-cell activation because T cells lack cystathionase, which converts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
594
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 792 publications
(609 citation statements)
references
References 46 publications
11
594
1
3
Order By: Relevance
“…These observations highlight the critical suppressive role of MDSCs in the tumor microenvironment of AML. MDSCs can exert the inhibition of T cell activation through multiple mechanisms including 1) depleting amino acids that are essential for T cell proliferation by overproduction of arginase 1 (ARG1); 30 2) causing the loss of T cell receptor by releasing oxidizing molecules (e.g. iNOS) and generating oxidative stress; 31,32 3) inducing the development of Treg; 33-36 and 4) impairing T cell migration by down regulating trafficking related surface molecules.…”
Section: Discussionmentioning
confidence: 99%
“…These observations highlight the critical suppressive role of MDSCs in the tumor microenvironment of AML. MDSCs can exert the inhibition of T cell activation through multiple mechanisms including 1) depleting amino acids that are essential for T cell proliferation by overproduction of arginase 1 (ARG1); 30 2) causing the loss of T cell receptor by releasing oxidizing molecules (e.g. iNOS) and generating oxidative stress; 31,32 3) inducing the development of Treg; 33-36 and 4) impairing T cell migration by down regulating trafficking related surface molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This shift in iNOS activity most likely reflects the crosstalk of iNOS with other enzymes such as NADPH oxidase to promote the production of peroxynitrites, which inhibits the proliferation and effector function of T cells [2]. MDSCs use several mechanisms in addition to the production of ROS and NO, such as triggering apoptosis of activated T cells by depleting of L-arginine, via arginase [7][8][9][10]. There is also evidence that MDSCs may suppress immune activation by inducing T regulatory cell expansion [11].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that MDSCs may suppress immune activation by inducing T regulatory cell expansion [11]. Other suppressive mechanisms that have recently been proposed include the production of TGF-β [12,13], depletion of cysteine [8], induction of COX2 and prostaglandin E2 [1,[14][15][16].Trypanosoma cruzi an obligate intracellular protozoan, is the causative agent of Chagas disease. This disease affects about 20 million people in Latin America, with 120 million persons at risk.…”
mentioning
confidence: 99%
“…Many factors have been previously implicated in the suppressive function of MDSCs, including the generation of reactive oxygen species (ROS) and NO by NADPH oxidase 41 and iNOS, 42 the deprivation of extracellular arginine and cysteine by arginase 42 and cysteine transporter X c À , 43 and Fas. 18 The suppressive function of MDSCs seems to be regulated by several transcription factors, including STAT3 and C/EBPb, and several recent studies have shown the STAT3-regulated suppressive functions of MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…24 Briefly, the syngeneic splenocytes were divided into equal numbers and either loaded with 1 lg/ml cytotoxic T lymphocyte (CTL) epitope peptide (human Her-2/neu p63 [TYLPTNASL] peptide or a mixture of E6 [41][42][43][44][45][46][47][48][49][50] [EVYD-FAFRDL] and E7 [49][50][51][52][53][54][55][56][57] [RAHYNIVTF] peptides) or left unpulsed. Peptide-pulsed splenocytes were labeled with chloromethylfluorescein diacetate succinimidyl ester (CFSE; Invitrogen, Carlsbad, CA) at 20 lM, and unpulsed splenocytes were labeled with 2 lM CFSE.…”
Section: In Vivo Cytotoxicity Assaymentioning
confidence: 99%